Upaya Meningkatkan Keterampilan Passing Bawah Bola Voli Melalui Variasi Latihan dengan Media Bola Karet Kelas XI MIPA SMAN 01 Marau - claudia, cindi (Journal Sport Academy, 2024)
This research aims to improve the learning outcomes of lower passing in the game of volleyball using rubber balls for students in class XI MIPA SMAN 01 Marau. The type of research is classroom action research (PTK) with two cycles. Data collection uses student test results. And the pre-cycle test shows that student learning outcomes are still very poor, there are 8 students in the incomplete category or 53.33%, then in the completed category there are 7 students or 40% of the total 15 students. After I used the rubber ball learning media in cycle I there were 10 students or 66.66% of the student category who completed, in the category of students who did not complete as many as 5 students or 33.33%. Meanwhile, based on the results of the final test in cycle II of 15 students in class 2 students or 13.33% then in the complete category there were 11 students or 86.66%. So it can be concluded that using rubber ball as a medium has been proven to improve students' learning outcomes for passing under volleyball. This is proven by the presence of rubber ball media. Volleyball underpassing skills are seen to have a very good ranking, namely that students' scores have increased in each cycle.